2014
DOI: 10.1016/j.radonc.2014.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Intrafractional tracking accuracy in infrared marker-based hybrid dynamic tumour-tracking irradiation with a gimballed linac

Abstract: Prediction errors were the primary cause of overall targeting errors, whereas mechanical errors were negligible. Furthermore, improvement of the prediction accuracy could be achieved by correcting systematic prediction errors in the previous field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 16 publications
1
50
1
Order By: Relevance
“…We previously showed that the intrafractional prediction errors in overall treatment were nearly identical to the training error for various respiratory motions. 13 However, in the present study, we found large differences between the Abbreviations: LR, left-right; CC, cranio-caudal; AP, anterior-posterior; 3D, three dimension. training error and the intrafractional prediction error when a 2,000 ms sampling interval was employed.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…We previously showed that the intrafractional prediction errors in overall treatment were nearly identical to the training error for various respiratory motions. 13 However, in the present study, we found large differences between the Abbreviations: LR, left-right; CC, cranio-caudal; AP, anterior-posterior; 3D, three dimension. training error and the intrafractional prediction error when a 2,000 ms sampling interval was employed.…”
Section: Discussioncontrasting
confidence: 62%
“…The second motion was acquired during beam delivery to reconstruct the 4D model, improving predictive accuracy. 7,13 The interval between the first and second respiratory motion acquisitions was 12.6 AE 3.1 min. Table I shows characteristics of the first and second respiratory motions.…”
Section: A Respiratory Motionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study, which evaluated the initial 10 patients from the present study cohort, confirmed high accuracies in the tracking performance. The 95th percentiles of overall tracking errors were 1.3 mm, 2.4 mm and 1.4 mm in left-right, cranio-caudal and anterior-posterior directions, respectively [22].…”
Section: Discussionmentioning
confidence: 91%